Data workflow for generating static geological model platform for petroleum prospect re-evaluation of Wytch Farm field, Wessex Basin, South Coast, United Kingdom - OSINOWO, Olawale Olakunle (Contributions to Geophysics and Geodesy, 2020)
The analyses and interpretation of the old existing 3D seismic and well log data of Wytch Farm field, Wessex Basin, south coast of the United Kingdom provided relevant information employed to generate static geological model platform. The platform which is requisite for building and distributing petrophysical and production data across the field could be useful for simulating the field’s performance, history matching as well as generate future prediction/forecast needful to establish the reasons for the early water breakthrough and sudden production decline from a peak value of 115,000 bbl/day in 1997 to the present production rate of less than 19,000 bbl/day. Six major faults which extend throughout the entire length of the field and five horizon surfaces which correspond to the top of Greensand, Combrash, Mercia mudstone and the top and base of Sherwood Formations aided the generation of the static geological model platform across the Wytch Farm field. The volume of delineated saturated reservoir rock lying above the Oil Water Contact (OWC) and enclosed within fault assisted anticlinal structures indicate a Gross Rock Volume (GRV) of 2,007,000,000 m3 and thus suggest that Wytch Farm field may likely still hold hydrocarbon potential beyond the present daily production rate. This potential could be unlocked through adequate reservoir management that requires detailed information such as could be generated from static geological model of the field.